Root Feeders: An Ecosystem Perspective - Johnson, Scott N (CABI, 2014)
Research on plants and their herbivores has traditionally been dominated by studies looking at interactions occurring aboveground, ranging from large mammals to the smallest invertebrates. The mechanisms and processes underpinning herbivory have been explored in almost all terrestrial ecosystems, ranging from agricultural monocultures to diverse forests and grasslands. Aboveground herbivory has been studied either ‘positively’ in terms of maximizing production of meat for human consumption, or ‘negatively’ in terms of controlling pest populations that reduce plant yields. By comparison, belowground herbivory by both vertebrates (e.g. rodents) and invertebrates (e.g. nematodes and insects) has been less well studied (Andersen, 1987; Brown and Gange, 1990; Hunter, 2001). Given that there is ample evidence from diverse ecosystems that >50% of net primary productivity is frequently allocated to the roots, which can approach 90% in some cases (Coleman, 1976), this seems to be paradoxical at first sight. The truth is that root feeders are, by their very nature, soil dwelling and therefore less visible, which has perhaps given rise to an ‘out of sight, out of mind’ attitude among researchers (Hunter, 2001). However, there is little doubt that root herbivores can be of considerable importance within an ecosystem. For example, root-xylem-feeding cicadas in eastern deciduous forests of North America have the highest collective biomass of any terrestrial animal when considered in terms of biomass per unit area (Karban, 1980).